Effects of Dry and Wet Ball Milling on the Structural and Optical Properties of ZnO Powder - Kim, Yerin; Lee, Ji Hyeon; Kim, Jea Hyung; Hong, Hyun Seon (Archives of Metallurgy and Materials, 2026)
Zinc oxide is a promising material for optoelectronic and UV-protection applications due to its biocompatibility, wide bandgap, and excellent optical properties. Since these properties are highly dependent on the microstructure, precise process control is essential for optimization. However, research on the high-value-added applications for ZnO recovered from industrial byproducts remains limited. In this study, the particle size and morphology of ZnO powder synthesized from waste zinc dust were controlled via dry and wet ball milling processes. The correlation between microstructural changes driven by milling conditions such as rotational speed and process method, and the resulting optical properties, including UV transmittance and photoluminescence, was systematically investigated. The results showed that the microstructure and UV transmittance of the ZnO powders changed distinctly depending on the milling parameters. Notably, the wet ball milling condition at 600 rpm achieved a minimum transmittance of 10.0%, demonstrating superior UV-shielding performance. This study demonstrates that the structural and optical properties of waste-derived ZnO powder can be effectively tuned through ball milling, suggesting the potential for utilizing industrial byproducts as functional UV-shielding materials.